2023
DOI: 10.3390/molecules28145443
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanism for Adsorption of Pb(II) Ions by Cu-BTC Metal–Organic Frameworks

Abstract: With the growing population, industrialization, and agriculture, water contamination not only affects people but entire ecosystems. Metal–organic frameworks (MOFs), because of their large surface area and porosity, show great potential as adsorbents for removing pollutants, such as heavy metals, from contaminated water. The current research aims at examining copper (II) benzene-1,3,5-tricarboxylate (Cu-BTC) MOFs and understanding the mechanism for their adsorption of Pb(II) from aqueous solution. The Cu-BTC sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Consequently, a gradually declining adsorption capacity was observed. Similar findings were reported in the literature [44,51].…”
Section: The Effect Of Cfbc-s Dosagesupporting
confidence: 93%
“…Consequently, a gradually declining adsorption capacity was observed. Similar findings were reported in the literature [44,51].…”
Section: The Effect Of Cfbc-s Dosagesupporting
confidence: 93%
“…When examining the sensitivity, selectivity, adsorption, and reusability, the use of certain functional organic ligands highlights the metal ions under specific circumstances and reduces the amount of experimental work required. It has been found that several organic materials, nanomaterials, and metalorganic frameworks have good kinetic performances and exhibit high Pb(II) ion adsorption rates [7][8][9][10][11][12][13][14][15][16][17]. However, it has continued to be difficult to regenerate conjugate adsorbent using strong acid, which produces secondary waste.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the context of porous materials, metal-organic frameworks (MOFs) are the focus of significant attention. MOFs are being considered for their potential application in numerous areas, ranging from adsorption and separation [ 4 , 5 , 6 ] to catalysis [ 7 , 8 ], luminescence [ 9 , 10 , 11 ], electronics [ 12 , 13 ], magnetism [ 14 ], drug delivery [ 15 ], and sensing [ 16 ]. To date, MOF materials have been developed into prospective resources for methane purification.…”
Section: Introductionmentioning
confidence: 99%